PEMBERDAYAAN TENAGA KERJA DALAM PENGELOLAAN AIR MINUM BERBASIS ISO: IMPLEMENTASI DALAM PROGRAM PENGABDIAN KEPADA MASYARAKAT - Putranto, Johni Harius (Program Studi Pendidikan Luar Sekolah, 2025)
High-quality drinking water is a fundamental necessity that requires management in accordance with standards ensuring quality, sustainability, and efficiency. This community service program aims to enhance workers' capacity in implementing an ISO-based Integrated Management System (IMS) at PT Meta Adya Tirta Umbulan, Pasuruan. The training covers five key ISO standards: ISO 9001:2015 (quality), ISO 14001 (environment), ISO 45001 (occupational health and safety), ISO 27001 (information security), and ISO 50001 (energy efficiency). Through a technical mentoring and hands-on training approach, workers have gained a better understanding of operational documentation, improved environmental management (indicated by the presence of fish in water channels), enhanced workplace safety procedures, data protection, and energy efficiency. These results demonstrate that applying an ISO-based IMS can enhance the effectiveness of the drinking water industry while benefiting the community as service recipients. Strengthening workforce capacity in integrated management standards should continue to ensure the sustainability of the drinking water industry, focusing on quality, safety, and environmental preservation.